Energy Conversion at the Cuticle of Living Plants. (24th October 2018) - Meder, Fabian; Must, Indrek; Sadeghi, Ali; Mondini, Alessio; Filippeschi, Carlo; Beccai, Lucia; Mattoli, Virgilio; Pingue, Pasqualantonio; Mazzolai, Barbara
Abstract: Progress towards green and autonomous energy sources includes harnessing living systems and biological tissue. It is recently discovered that the cuticle‐cellular tissue bilayer in higher plant leaves functions as an integrated triboelectric generator conductor couple capable of converting mechanical stimuli into electricity. Here, it is investigated for the first time, in detail how charge generation at the living plant leaf occurs, and it is shown how whole plants could be used in plant‐hybrid wind‐energy harvesting systems. The charge accumulation and compensation in and ex vivo on Rhododendron leaves by Kelvin force microscopy is verified, revealing that charges are induced and transported in living plant tissue whereas charges remain unbalanced and trapped on dead leaves of the same species. A distinct sensing functionality and opportunity to upscale power output is given as electrical signals are species, touch‐material, and dose‐dependent and scale with frequency, impact force, and area. It is shown that also purely natural mechanical stimuli by wind or self‐touching of leaves are converted into electrical signals by a triboelectric mechanism. The entirely plant‐enabled and autonomous energy conversion can be used to directly drive light emitting diodes, charge a capacitor, and harvest wind‐energy with promise for new energy sources based on the Plant Kingdom. Abstract : Living plants integrate energy conversion and conduction networks in a single organism that can be used as natural triboelectric generators . It is investigated in detail how charge generation occurs at the plant leaf cuticle, world's largest biointerface, and the effect is used to construct plant‐hybrid energy converters, e.g., for wind‐energy harvesting.